Data for improved water management in Colorado's Arkansas River basin: hydrological and water quality studies - Gates, Timothy K., author; Steed, Gregory H., author; Niemann, Jeffrey D., author; Labadie, John W., author; Colorado Water Institute, publisher (Colorado State University. Libraries, 2016)
Colorado water law is complicated and can easily be misunderstood. In particular, the component of a water right that requires it be put to a beneficial use without waste can create confusion. It is a fact that wasteful water diversions and practices are not permissible under the state's water law. Unfortunately, this has led to the adoption of the misleading adage "Use It or Lose It." This document clarifies how the use or nonuse of a water right affects its value.
Keywords: Water-supply; Irrigation water; Water quality; assessment; Upper Arkansas River Watershed; Colorado